Երկրագործական տարածքներն ու ոռոգման համակարգը հյուսիսարևմտյան Իրանում ըստ սեպագիր աղբյուրների - Երվանդ Գրեկյան (ՀՀ ԳԱԱ հրատ.)
В статье рассматриваются 12 терминов, которые встречаются в "Луврской табличке" ассирийского царя Саргона II. Пять из них (nagū, а.ša, a.gar, tamertu,qarbatu) относятся к земледельческой терминологии, остальные семь (ID, palgu, atappu. hiritu, halilu, hirişu, AB.SIN) — к терминологии искусственного орошения.12 terms mentioned in the "Louvre Tablet" of the Assyrian King Sargon II are discussed in the article. Five of them refer to agricultural terminology (nagū, a.ša, a.gar, tamertu, qarbatu) and seven (ID, palgu, atappu, hiritu, halilu, hirişu, AB.SIN) - to that of artificial irrigation.
Keywords: History; Agriculture; Auxiliary Sciences of History; Ancient History; Technology; Hydraulic engineering; Ocean engineering; Inscriptions; Epigraphy; D History